Liber, Augustus and Mark Antony - Serignolli, Lya (Revista Archai, 2024)
Libertas was an essential issue in Roman politics, connected to the beginnings of the Republic; and Liber was a divinity that corresponded to this aspect from different perspectives. Liber and libertas, especially in politics, were deeply rooted in the Roman mind, and political leaders found it interesting to establish this connection. Between the forties and the thirties BC, several political leaders adopted divinities as patrons and models. In the context of civil war, the struggle for power was presented in poetry as a confrontation between divine models. This article investigates the role of Bacchus as a divine model for political leaders in Horace, focusing on his associations with Augustus and Mark Antony/Cleopatra. My aim is to show how Horace, taking advantage of the god’s paradoxical character, contributes to the assimilation of Liber to the Augustan repertoire in a moment of profound political transformations in Rome.